2017
DOI: 10.1016/j.econmod.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Gold and inflation(s) – A time-varying relationship

Abstract: What is the relationship between the price of gold and inflation? How stable is it -over time and across measures of inflation? We examine this for three countries (the USA, the UK and Japan) over forty years and with a variety of measures of inflation and monetary liquidity. We apply a formal test for time variation and proceed to extract time varying cointegration relationships. Both formal and graphical evidence points to a break in the relationship(s) of gold and official inflation in the mid 1990s in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 56 publications
2
50
0
2
Order By: Relevance
“…For example, Iqbal () reported that gold hedges inflation risk in the United States only during average and bearish conditions of the gold market but not during bullish trends. Lucey, Sharma, and Vigne () found evidence for a time‐varying cointegration relationship between gold and both predicted and realized inflation. Moreover, previous studies shed no light on the causality between gold returns and inflation expectation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Iqbal () reported that gold hedges inflation risk in the United States only during average and bearish conditions of the gold market but not during bullish trends. Lucey, Sharma, and Vigne () found evidence for a time‐varying cointegration relationship between gold and both predicted and realized inflation. Moreover, previous studies shed no light on the causality between gold returns and inflation expectation.…”
Section: Introductionmentioning
confidence: 99%
“…Second, Lucey et al . () found that the relationship between gold and measures of inflation and monetary liquidity in three countries (the United States, the United Kingdom, and Japan) is time‐varying. It would hence be interesting to find out whether the relationship between global liquidity and gold is also time‐varying.…”
Section: Resultsmentioning
confidence: 99%
“…My hypothesis hence is that the gold price would be influenced by the gap between real money and real output. Furthermore, gold could co‐move with inflation as Figure indicates over the first half of the sample, while this relationship may have broken down during the 1990s (similar to the country‐level findings by Lucey et al ., ). How could these visual observations be interpreted?…”
Section: Empirical Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Here the examples are numerous, particularly in regards to strategic metals (rare-earth elements such as indium, iridium, rhodium) and precious metals. Recent contributions include Batten et al (2010), Aruga and Managi (2011), Mancheri andMarukawa (2016), O'Connor et al (2015), Lucey et al (2016), Ge et al (2016), and Lau et al (2017) -see also the special issue on white metals in this journal. Indeed, in that spirit, a change in the nature of white precious metals can be observed, shifting from commodities to investment assets (Vigne et al (2017)).…”
Section: Commodity Marketsmentioning
confidence: 99%